Physical properties of co-crystallized bitter orange: effect of pH, soluble solids and added juice - Andrade Pizarro, Ricardo David (2017)
The aim of this study was to evaluate the conditions of co-crystallization of bitter orange juice with sucrose on the physicochemical properties of the product. Bitter orange juice was obtained with a mechanical juicer and concentrated on a rotary evaporator. Sucrose syrup 70 oBrix was subjected to heating and stirring of 1000 rpm, until a white color (118 °C) was observed. Bitter orange juice was added to the syrup, and the mixture was subjected to constant stirring of 600 rpm, to observe the formation of a particulate solid material. The co-crystals were dried, grinded and sieved. A dry co-crystal was determined: moisture, bulk density, solubility, water activity and repose angle. High proportion of bitter orange juice added (20%) and low content of soluble solids (50 °Brix) produced co-crystals with low moisture content (2.59%), water activity (0.52) and solubility time (69.4 s). High pH (4.5) of bitter orange juice concentrate produced co-crystals with low moisture contents (1.96%). The co-crystals of bitter orange juice showed good reconstitution characteristics (high solubility); however, these had high humidity (2.5 to 4.5%) and water activity (0.508 to 0.798).